DIAGENESIS RESERVOIR BATUAN KARBONAT DI LAPANGAN MUDI CEKUNGAN JAWA TIMUR UTARA - WIDYANTORO, SURYA
Mudi oil field is located in Tuban Kota District, Tuban Area, approximately 120 km western of Surabaya City, Jawa Timur Province. Since 1998 the field started produce oil with high rate of production which come from carbonate rocks reservoir equivalen Tuban Formation. This carbonate rocks hypothetized have complex facies, diagenesis and porosity which interested to be analized more detail. The main goal of this research is to understand processes which affect and control different porosity value in wells of Mudi Field based on diagenesis analysis approach. Research method mainly using macroscopic and microscopic lithology analysis from cutting and core of Mudi-4 and Mudi-9 wells. Also support by logging, seismic and routine core laboratory test results. From research analyses and interpretation, is resulted that carbonate rocks equivalen Tuban Formation has 2 (two) types facies group consist of first facies group in top depth interval are large foram packstone withred algae and coral, and fasies kedua and second facies group in bellow depth interval are large foram packstone/wackstone/mudstone with bioklastik red algae dan coral. Depositional environment of this carbonate rocks is open lagoon with many patch reefs. Diagenetic process took in place since early diagenetic phase to porosity erotional phase until late burial diagenetic phase. Diagenetic can be seen in shape of dissolution, cementation, vuggy pore to dolomitization and stylolites structure from pressure/compaction. Facies type and development of diagenetic phase, besides of late charging system, are giving strong effect to low porosity value distribution of carbonate rocks in this field.